Optimization of Inner Bilge Design to Enhance Cargo Tank Capacity in Tankers - Yulianto, Ardi Nugroho; Winarko, Raybonda Reinaldi; Pasaribu, Sheely Leony Artha; Ahmad, Roisul Fadli; Adietya, Berlian Arswendo; Hasanudin, Hasanudin (Department of Naval Architecture - Diponegoro University, 2026)
The world of shipping industry keeps evolving to develop the most efficient ship designs, including tanker ship designs. According to MARPOL Annex 1 Regulation 19, oil tankers over 600 deadweight and built after 6 July 1996 must have wing tank and double bottom structures, which significantly reduce the cargo hold volume. Therefore, the objective of this research is to optimize the cargo hold volume by converting the conventional sloped hopper into a rounded inner bilge configuration. The optimization problem is formulated with the cargo oil tank volume as the objective function to be maximized. The design variables include the inner bilge radius and the positions of two cargo landing points at each knuckle along the cargo oil tank, defined in transverse and vertical coordinates. The constraints consist of regulatory and design requirements, including clearance, stability, freeboard, and longitudinal strength. Grid search method is employed to systematically evaluate all possible combinations of design variables, ensuring identification of the global optimum. The optimisation process is automated using Visual Basic for Applications (VBA) integrated with ship modelling software. The research resulted in a new design that increased the cargo oil tank volume by 0.960%. A sister ship with the same payload could be built with an optimized cargo oil tank design configuration by reducing the length of the cargo oil tanks and the ship itself. However, this improvement comes with a trade-off in terms of practical applicability during the shipbuilding process.